Survival Outcomes of Epithelial Ovarian Cancer Patients Following Dose-dense Versus 3-Weekly Platinum–Paclitaxel Chemotherapy: A Meta-Analysis. Issue 2 (February 2023) - Pergialiotis, V.; Liatsou, E.; Thomakos, N.; Liontos, M.; Frountzas, M.; Papapanagiotou, A.; Rodolakis, A.; Haidopoulos, D.
Abstract: Aims: Dose-dense chemotherapy has proven its value in several cancer fields. The purpose of the present systematic review is to evaluate the impact of dose-dense chemotherapy on survival outcomes of epithelial ovarian cancer patients. Materials and methods: Medline, Scopus, the Cochrane Central Register of Controlled Trials CENTRAL, Google Scholar and Clinicaltrials.gov databases were searched for relevant articles. Effect sizes were calculated in Rstudio using the meta and metafor functions. A sensitivity analysis was carried out to evaluate the possibility of small study effects and P- hacking. The methodological quality of the included studies was assessed using Risk of Bias 2 (RoB2) and Risk of Bias in non-Randomized Trials (RoBINS) tools. Results: Overall, 12 studies were included in the present systematic review, involving 4979 epithelial ovarian cancer patients. The risk of recurrence was substantially improved in patients receiving dose-dense chemotherapy (hazard ratio 0.82, 95% confidence interval 0.70, 0.96); however, the result of the meta-analysis may be attributed to the effect size of smaller studies as following adjustment for small study effects the outcome becomes non-significant (hazard ratio 0.91, 95% confidence interval 0.81, 1.02, P = 0.123). Overall survival rates were not improved by dose-dense chemotherapy (hazard ratio 0.79, 95% confidence interval 0.60, 1.04). Thirty-five types of adverse effect were identified following retrieval of data from the original studies. Dose-dense chemotherapy did not increase significantly the rates of severe adverse effects, although thrombosis, severe diarrhoea and severe nausea were more prevalent in this group of patients. Conclusion: Dose-dense chemotherapy is associated with comparable side-effects to those of standard chemotherapy; however, data related to survival outcomes are not positive; hence, its use outside the setting of clinical trials should be discouraged.